2018
DOI: 10.1002/clen.201800099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Two‐Tier Fibrous Membrane by Sequential Electrospinning for Effective Air Filtration

Abstract: In the current work, a strategy to fabricate two‐tier structured poly l‐lactide/TiO2 nanoparticles (NPs) incorporated polyvinylpyrrolidone (PLLA/PVP‐TiO2 NPs) fibrous membrane for air filtration via sequential electrospinning technique are reported. Anatase TiO2 NPs ranging from 90 to 105 nm in size were synthesized by the sol–gel method. The diameter of PLLA and PVP‐TiO2 NPs fibers was in the range of 1.15–1.45 and 1.8–2.2 μm, respectively. This two‐tier membrane possessed thermal stability with decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In the temperature range of 500–600 °C, the membrane mass does not indicate any further significant loss, with only P25 TiO 2 NPs remaining. The slight increase in weight above 600 °C is due to a phase transition of the P25 TiO 2 NPs from anatase to rutile . The actual loading of P25 TiO 2 NPs in PLLA@TiO 2 membranes can only be obtained in the temperature range of 500–600 °C, which are determined to be approximately 63.0% for p-PLLA@TiO 2 -1, 47.1% for p-PLLA@TiO 2 -0.5, 31.6% for p-PLLA@TiO 2 -0.25, and 16.5% for p-PLLA@TiO 2 -0.1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the temperature range of 500–600 °C, the membrane mass does not indicate any further significant loss, with only P25 TiO 2 NPs remaining. The slight increase in weight above 600 °C is due to a phase transition of the P25 TiO 2 NPs from anatase to rutile . The actual loading of P25 TiO 2 NPs in PLLA@TiO 2 membranes can only be obtained in the temperature range of 500–600 °C, which are determined to be approximately 63.0% for p-PLLA@TiO 2 -1, 47.1% for p-PLLA@TiO 2 -0.5, 31.6% for p-PLLA@TiO 2 -0.25, and 16.5% for p-PLLA@TiO 2 -0.1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The burning cigarette is fixed at the nozzle of inlet tube of the filtration setup, and besides, the outlet tube of the filtration setup is connected to a pump. A digital particulate concentration sensor (PMS7003, Beijing Plantower Co., Ltd) was used to measure the particle concentrations both before and after the filtration [11,27]. Five specimens for each sample were measured, followed by the calculation of arithmetic mean.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, plenty of researches have been conducted to improve filtration efficiency by taking advantage of electrospun nanofibers. In the past few days, Ramachandran and Rajiv [11] reported a two-tier fibrous membrane fabricated by electrospinning that displayed an outstanding adsorption capability of air pollutants and great dust filtration capability. Balgisand et al [12] found that the filtration efficiency of filter, which was made from straight and bead-free electrospun nanofibers, increased with the decreasing of fiber diameter.…”
Section: Introductionmentioning
confidence: 99%
“…19 Also, Ramachandran and Rajiv produced two-tier structured electrospun fibrous layers that facilitated the adsorption and filtration of airborne pollutants. 20 In the study reported here, melt-blowing and electrospinning techniques were employed to produce micro-nano composite membranes that can restore surface charges for gradient filtration against PM. A very small amount of PTFE electret powders was mixed with PP, which allows PTFE to be wrapped in PP that has good mobility and a low melting point.…”
Section: Introductionmentioning
confidence: 99%
“…combined polyacrylonitrile and graphene oxide to increase the surface roughness 19 . Also, Ramachandran and Rajiv produced two‐tier structured electrospun fibrous layers that facilitated the adsorption and filtration of airborne pollutants 20 …”
Section: Introductionmentioning
confidence: 99%